Fay Jones' Stoneflower: Eden Isle, Arkansas - Richard W. Longstreth (Oz, 1983)
Among the numerous buildings designed by Fay Jones in the central United States during the past quarter century, some of the most remarkable have been born out of highly constrained programs…